2009
DOI: 10.1177/0169796x0902500104
|View full text |Cite
|
Sign up to set email alerts
|

Microfinance and Rural Household Development

Abstract: Though at the theoretical level, micro-credit is said to play a significant role in poverty reduction, empirical work on the role of micro-credit in poverty reduction is mixed with some studies indicating high levels of employment and income generation and others suggesting a worsening of poverty with micro-credit. Does micro-credit really get to the poor? Does it enhance or impede their productivity? Based on a study of 139 households in one rural area in the Upper West Region of Ghana, we find that: (a) Bene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 17 publications
3
24
0
1
Order By: Relevance
“…Besides receiving financial benefits, villagers in Pesantren Village also attained other benefits such as improvement in environmental conditions (expansion of mangrove plantation, increase in land productivity and intensity of mangrove aquaculture) and increased in capacity to develop mangrove based business alternatives. This evidences showed that Government assistance to the poor does not always create people dependency and disincentives that make things not better but worse, like what has been argued by Morduch (1999) and Kutir and Odoom (2009).…”
Section: Perception On the Bio-rights Schemementioning
confidence: 61%
“…Besides receiving financial benefits, villagers in Pesantren Village also attained other benefits such as improvement in environmental conditions (expansion of mangrove plantation, increase in land productivity and intensity of mangrove aquaculture) and increased in capacity to develop mangrove based business alternatives. This evidences showed that Government assistance to the poor does not always create people dependency and disincentives that make things not better but worse, like what has been argued by Morduch (1999) and Kutir and Odoom (2009).…”
Section: Perception On the Bio-rights Schemementioning
confidence: 61%
“…The loans provided by the MFIs have had great impact on the agriculture sector. Since the farmers are able to secure capital through the MFIs, they can buy farm tools and equipment as well as generate income to reduce poverty and take care of families, and develop their communities' income (Angko, 2013;Kotir & Obeng-Odoom, 2009). Consequently, in certain parts of the continent, the microfinance sector comprises many microfinance institutions that are mostly concentrated around big cities.…”
Section: "In the Eu Context Microcredit Has Been Defined In 2003 As mentioning
confidence: 99%
“…Access to loans and other credit facilities to individuals and SMEs has the potential to reduce poverty, facilitate women empowerment in developing countries (Ganu & Boateng, 2012), development of the informal sector (Al Mamun, 2012;Boateng et al, 2013;Dary & Haruna, 2013), reduce poverty (Adjei et al, 2009;Angko, 2013), and facilitate rural household and economic development (Ganu & Boateng, 2012;Kotir & Obeng-Odoom, 2009). …”
Section: Loan/credit Facility In Ghanaian Financial Marketmentioning
confidence: 99%
See 1 more Smart Citation
“…Microfinance profitability totally relies on retaining the clients' loyalty and clients' satisfaction (Nawaz, 2010;Shahriar, 2012). Satisfied clients attract new clients by word-of-mouth communication which has a very high inducement factor to maximize membership participation into the microfinance organizations (Kotir & Obeng-Odoom, 2009;Shahriar, 2012). Microfinance practitioners have realized the importance of customer satisfaction and retention and they have even come to the conclusion that it costs them more to acquire new customers than to satisfy and retain the existing customers (Westover, 2008;Islam, 2011).…”
Section: Introductionmentioning
confidence: 99%